Protective effect of Lactobacillus salivarius Li01 on thioacetamide‐induced acute liver injury and hyperammonaemia. Issue 6 (11th July 2020) - Yang, Liya; Bian, Xiaoyuan; Wu, Wenrui; Lv, Longxian; Li, Yating; Ye, Jianzhong; Jiang, Xianwan; Wang, Qing; Shi, Ding; Fang, Daiqiong; Wu, Jingjing; Wang, Kaicen; et al.
Summary: The gut microbiota plays pivotal roles in liver disease onset and progression. The protective effects of Lactobacillus salivarius Li01 on liver diseases have been reported. In this study, we aimed to detect the protective effect of L. salivarius Li01 on thioacetamide (TAA)‐induced acute liver injury and hyperammonaemia. C57BL/6 mice were separated into three groups and given a gavage of L. salivarius Li01 or phosphate‐buffered saline for 7 days. Acute liver injury and hyperammonaemia were induced with an intraperitoneal TAA injection. L. salivarius Li01 decreased mortality and serum transaminase levels and improved histological liver damage caused by TAA. Serum inflammatory cytokine and chemokine and lipopolysaccharide‐binding protein (LBP) concentrations, nuclear factor κB (NFκB) pathway activation and macrophage and neutrophil infiltration into the liver were significantly alleviated by L. salivarius Li01. L. salivarius Li01 also reinforced gut barrier and reshaped the perturbed gut microbiota by upregulating Bacteroidetes and Akkermansia richness and downregulating Proteobacteria, Ruminococcaceae_UCG_014 and Helicobacter richness. Plasma and faecal ammonia levels declined noticeably in the Li01 group, accompanied by improvements in cognitive function, neuro‐inflammation and relative brain‐derived neurotrophic factor (BDNF) gene expression. Our results indicated that L. salivarius Li01 could be considered a potential probiotic in acute liver injury and hepatic encephalopathy (HE). Abstract : Lactobacillus salivarius Li01 improved TAA‐induced acute liver injury and hyperammonemia which was mediated by restoring destroyed gut microbiota and barrier function, improving TAA‐induced liver damage and systemic inflammation, and alleviating hyperammonaemia, neuro‐inflammation and damaged cognitive function.